KAJIAN PUSTAKA PENYAKIT TROPIS TERABAIKAN : ASPEK HOLISTIK PADA PASIEN KUSTA DAN FILARIASIS - Retno Ardanari Agustin (coba, 2020)
Introduction: Neglected Tropical Disease (NTD) is a tropical and sub-tropical disease that is still experienced by many people with weak economic conditions and tends to be neglected due to various factors. The problems experienced by patients with NTD are very complex, ranging from physical conditions experiencing weakness, changes due to disability and its effects after experiencing physical changes. Method: this study used a literature method on the holistic aspects of leprosy and filariasis patients in 2009-2019 and is supported by secondary data from the Health Office of Kediri Regency. Results: Leprosy patients in East Java with level 2 disability was 10.40% while filariasis patients were 10,681 cases. Leprosy and filariasis patients experienced various problems in the holistic aspects of their lives due to their physical deformity, so they feel ashamed to get along with people around them and limit social interactions, decreased productivity, depending on others, patients and families being exiled, difficult to find work. Conclusion: Leprosy and filariasis patients experience changes and physical disturbance due to the disease process that affected other aspects such as psychological, social, spiritual and cultural in patients, families.